Some Comments on the Legal Regulation on Misinformation and Cyber Attacks Conducted Through Online Platforms - Mezei, Kitti; Szentgáli-Tóth Boldizsár (LeXonomica, 2023)
What are the tools to effectively manage the new threats to the free flow of opinions to protect this essential precondition for a pluralist social and political system? As a basis for action at the community level, how can we protect users who use internet platforms to inform themselves on issues of public interest from disinformation attacks through cyberspace? Effective action against cyber-attacks that adversely affect certain fundamental rights requires a combination of instruments, creating the technological, economic, human and legal conditions for meaningful counter-measures. In legal terms, the guarantees that platform providers must offer each user to prevent cyber attacks and illegal content should be laid down, and legal instruments should be put in place to ensure they are always available. In addition, in the event of misusing any content shared on the platform or of personal data made available to the operator, clear responsibilities should be established, and the extent to which the responsibility for protection lies with the platform operator or the user should be clarified. In our study, we outline regulatory options to address these challenges. Povzetek Kakšna so orodja za učinkovito obvladovanje novih groženj prostemu pretoku mnenj, da bi zaščitili ta bistveni pogoj za pluralni družbeni in politični sistem? Kako lahko uporabnike, ki uporabljajo spletne platforme za informiranje o vprašanjih javnega interesa, zaščitimo pred dezinformacijskimi napadi v kibernetskem prostoru kot podlago za ukrepanje na ravni skupnosti? Za učinkovito ukrepanje proti kibernetskim napadom, ki negativno vplivajo na nekatere temeljne pravice, je potrebna kombinacija instrumentov, ki ustvarjajo tehnološke, gospodarske, človeške in pravne pogoje za smiselne protiukrepe. V pravnem smislu je treba določiti jamstva, ki jih morajo ponudniki platform ponuditi vsakemu uporabniku za preprečevanje kibernetskih napadov in nezakonitih vsebin, ter vzpostaviti pravne instrumente, da bodo vedno na voljo. Poleg tega bi bilo treba v primeru zlorabe katere koli vsebine, ki se deli na platformi, ali osebnih podatkov, ki so na voljo upravljavcu, določiti jasne odgovornosti in pojasniti, v kolikšni meri je za zaščito odgovoren upravljavec platforme ali uporabnik. V naši študiji opisujemo regulativne možnosti za reševanje teh izzivov.